Comprehensive metabolic study of IOX4 in equine urine and plasma using liquid chromatography/electrospray ionization Q Exactive high‐resolution mass spectrometer for the purpose of doping control. Issue 2 (21st October 2021) - Ishii, Hideaki; Shibuya, Mariko; So, Yat‐Ming; Wong, Jenny K. Y.; Ho, Emmie N. M.; Kusano, Kanichi; Sone, Yu; Kamiya, Takahiro; Wakuno, Ai; Ito, Hideki; Miyata, Kenji; Yamada, Masayuki; et al.
Abstract: IOX4 is a hypoxia‐inducible factor prolyl hydroxylase (HIF‐PHD) inhibitor, which was developed for the treatment of anemia by exerting hematopoietic effects. The administration of HIF‐PHD inhibitors such as IOX4 to horses is strictly prohibited by the International Federation of Horseracing Authorities and the Fédération Équestre Internationale. To the best of our knowledge, this is the first comprehensive metabolic study of IOX4 in horse plasma and urine after a nasoesophageal administration of IOX4 (500 mg/day, 3 days). A total of four metabolites (three mono‐hydroxylated IOX4 and one IOX4 glucuronide) were detected from the in vitro study using homogenized horse liver. As for the in vivo study, post‐administration plasma and urine samples were comprehensively analyzed with liquid chromatography/electrospray ionization high‐resolution mass spectrometry to identify potential metabolites and determine their corresponding detection times. A total of 10 metabolites (including IOX4 glucuronide, IOX4 glucoside, O ‐desbutyl IOX4, O ‐desbutyl IOX4 glucuronide, four mono‐hydroxylated IOX4, N ‐oxidized IOX4, and N ‐oxidized IOX4 glucoside) were found in urine and three metabolites (glucuronide, glucoside, and O ‐desbutyl) in plasma. Thus, the respective quantification methods for the detection of free and conjugated IOX4 metabolites in urine and plasma with a biphase enzymatic hydrolysis were developed and applied to post‐administration samples for the establishment of elimination profiles of IOX4. The detection times of total IOX4 in urine and plasma could be successfully prolonged to at least 312 h. Abstract : An administration of IOX4 to three thoroughbred mares was conducted. Plasma and urine samples obtained after administration were comprehensively analyzed with liquid chromatography high‐resolution mass spectrometry and it was found that IOX4 and IOX4 glucuronide mainly existed in plasma whereas IOX4 glucuronide and IOX4 glucoside were the major urinary metabolites. For the purpose of doping control in horses, the detection of total (free and conjugated) IOX4 was deemed to be more appropriate and effective.